2017
DOI: 10.1016/j.molimm.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of activated human CD8 T cells with IL-12 leads to enhanced TCR-induced signaling and cytokine production

Abstract: During the immune response to pathogens and autoantigens, CD8 T cells are exposed to numerous inflammatory agents including the cytokine IL-12. Previous studies have focused on how IL-12 regulates T cell functions when present during or after the activation of the T cell receptor (TCR). However, recent studies suggest that prior exposure to IL-12 also alters the TCR responsiveness of murine T cells. Whether similar phenomena occur in human activated CD8 T cells and the mechanisms mediating these effects remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…When we analyzed all of our data for correlations, we found significant correlations between plasma cytokine abundance and measures of T cell metabolism, which were unique in patients with ME/CFS compared with controls. ME/CFS CD8 + T cell glycolysis had multiple significant correlations with cytokines that are known to be proinflammatory or with growth factors (63)(64)(65). This is especially interesting, given the reduced basal glycolysis we observed in patients with ME/CFS.…”
Section: Methodsmentioning
confidence: 61%
“…When we analyzed all of our data for correlations, we found significant correlations between plasma cytokine abundance and measures of T cell metabolism, which were unique in patients with ME/CFS compared with controls. ME/CFS CD8 + T cell glycolysis had multiple significant correlations with cytokines that are known to be proinflammatory or with growth factors (63)(64)(65). This is especially interesting, given the reduced basal glycolysis we observed in patients with ME/CFS.…”
Section: Methodsmentioning
confidence: 61%
“…Interestingly, STAT4 is required for the production of IFN-γ downstream of IL-12 in both CD4 + and CD8 + T cells, but only CD4 + T cells require IL-12 and STAT4 for the production of IFN-γ following antigen recognition and T cell receptor (TCR) signaling suggesting alternative regulatory pathways in different lymphocyte subsets (Trinchieri, 2003[ 184 ]; Carter and Murphy, 1999[ 30 ]). It was also shown that IL-12 pre-treatment of CD4 + and CD8 + T cells enhances TCR-induced IFN-γ, tumor necrosis factor alpha (TNF-α), IL-13, IL-4 and IL-10 production and intensifies oxidative metabolism (Vacaflores et al, 2016[ 191 ], 2017[ 192 ]).…”
Section: Cellular Functions Of Il-12mentioning
confidence: 99%
“…IL-12 is a main proinflammatory cytokine that stimulates T-cell responses by priming them for IFN-γ production, inducing apoptosis of regulatory T-cells, and increasing CD8 + T-cell infiltration ( 94 97 ). Furthermore, adoptive transfer of CD8 + T-cells engineered to secrete IL-12 enhanced responses in a murine model of melanoma by reprogramming MDSCs ( 98 ).…”
Section: Discussion: Strategies To Befriend the Tme In Car T-cell Thementioning
confidence: 99%